PENGARUH PENAMBAHAN WAJIB PAJAK BADAN, PENYAMPAIAN SPT MASA PPH BADAN, PENERBITAN SURAT TAGIHAN PAJAK DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN BADAN - Yessi Arisandi; Vince Ratnawati; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aim is to examine the effect of the addition of corporate taxpayers, the delivery of notification period letter, the publication of tax bill and tax audit to the corporate income tax receipts. This research used probability sampling method and multiple linear regression analysis test with the help of the program SPSS version 16.0. The source of data in this research is a secondary data from KPP Pratama Pekanbaru Senapelan period 2010-2014. The results of research indicated that the addition of corporate taxpayers, the delivery of notification period letter, the publication of tax bill and tax audit have a simultaneous significant effect to the corporate income tax receipts. Partially, only the delivery of notification period letter of corporate income tax has no significant effect to the corporate income tax receipts. While the addition of corporate taxpayers, the publication of tax bill and tax audit have a significant effect to the corporate income tax receipts.Keywords:The corporate income tax receipts, the addition of corporate taxpayers, the delivery of notification period letter, the publication of tax bill, tax audit.